Sex-differences in response to arm and leg ergometry in juvenile judo athletes - Pocecco, E.; Burtscher, M. (Archives of Budo, 2013)
Background and Study Aim: Literature deals barely with sex-related differences of young judokas concerning physiological data from laboratory tests. Therefore, the aim of this study was the knowledge about the similarities and differences of the juvenile male and female judo athletes, derived from all-out arm and leg ergometric tests of combat duration. Material and Methods: Maximum power output (Pmax) and physiological indicators, i.e., peak oxygen uptake (VO2peak), peak ventilation (VEpeak), peak heart rate, post-exercise lactate (LA), and rate of perceived exertion (RPE), of 17 male (14.0±1.4 years) and 6 female (13.8±1.3 years) juvenile Austrian judo athletes were assessed during incremental tests of combat duration (~ 3-4 min) on an arm crank and a cycle ergometer. Results: Juvenile men had about half of women`s %fat (10.6±3.3% vs. 20.2±3.8%, p=0.01), higher values of relative Pmax (2.5±0.3 W·kg-1 vs. 2.0±0.2 W·kg-1, p=0.01), absolute and relative VO2peak (2201.9±559.0 ml·min-1 vs. 1667.2±341.5 ml·min-1, p=0.05 and 38.4±4.9 ml·kg-1·min-1 vs. 29.8±4.6 ml·kg-1·min-1, p=0.01), relative VEpeak (1.6±0.3 l·kg-1·min-1 vs. 1.2±0.3 l·kg-1·min-1, p=0.01), and LA (9.3±2.5 mmol·l-1 vs. 6.5±1.2 mmol·l-1, p=0.05) during arm ergometry and higher values of relative VO2peak (51.8±6.0 ml·kg-1·min-1 vs. 45.3±4.5 ml·kg-1·min-1, p=0.05) and RPE concerning breathing effort during cycling (16.4±1.6 vs. 14.6±1.5, p=0.05). Conclusions: The present results demonstrate sex-specific differences performance indicators assessed during arm and leg ergometry of combat duration in juvenile judo athletes. These findings may have practical importance and should be considered in evaluating the results from ergometric testing as well as in planning the training for young male and female judo athletes.